Pengembangan Media Pembelajaran Herbarium Barcode pada Materi Pteridophyta - Krisdayanti Krisdayanti; Anandita Eka Setiadi; Ari Sunandar (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
Generation Z students like things related to smartphones as well as practical and interesting teaching materials. This research aims to determine the validity value and students' responses to barcode herbarium teaching material products on pteridophyta material. Researchers use the R&D method with the Borg and Gall development model, including stages: 1) research and data collection; 2) planning; 3) product development; 4) initial field trials; 5) trial revision; 6) field trials; and 7) improvement of the resulting product. The tools used for data collection were validation questionnaires and student responses. The assessment results show that the media that has been developed is very valid in the media aspect (95%) and material (90.47%), and valid in the language aspect (80%). Students gave very good responses to the herbarium barcode learning media in small-scale trials (83.97%), as well as large-scale trials (84.56%), it was concluded that the media developed was effective and received very good responses from students.